2020
DOI: 10.1177/1369148119893633
|View full text |Cite
|
Sign up to set email alerts
|

The ‘internationalisation agenda’ and the rise of the Chinese university: Towards the inevitable erosion of academic freedom?

Abstract: This essay is a critical reflection on the challenge to academic freedom presented by the globalisation of practices of knowledge production. It explores a tension within the logic of the internationalisation agenda: UK universities are premised upon forms of knowledge production whose roots lie in European Enlightenment values of rationalism, empiricism and universalism, yet partnerships are growing with universities premised on rather different, non-liberal and, perhaps, incommensurable values. Therefore, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
4
0
2
Order By: Relevance
“…Lecturers understand this freedom as freedom from campus, government, industry, and religion, ethnicity, and gender. The results of this research reinforce the notion that general academic freedom is open to the possibility of interpretation and debate [33,34]. Textually the general statement of academic freedom is seen in the document [35].…”
Section: Discussionsupporting
confidence: 80%
“…Lecturers understand this freedom as freedom from campus, government, industry, and religion, ethnicity, and gender. The results of this research reinforce the notion that general academic freedom is open to the possibility of interpretation and debate [33,34]. Textually the general statement of academic freedom is seen in the document [35].…”
Section: Discussionsupporting
confidence: 80%
“…On the one hand, societal factors influence what universities can and cannot do, which is most clear for the topic of academic freedom. Panellists suggested that the role of individual universities in cultivating and safeguarding academic freedom is fairly constrained, as exercising and protecting academic freedom is difficult in politically unstable or authoritative states (Owen, 2020;. On the other hand, many of the responsibilities can be shared by universities collectively.…”
Section: Discussionmentioning
confidence: 99%
“…A more critical reading of globality thus recognises stratification within and between cores and peripheries (Cheng and Brettle, 2019; Cox and Nossal, 2009; Kristensen, 2015). Furthermore, as universities in the non-West climb international rankings, bringing with them alternative epistemological and pedagogical practices, academic perceptions of what constitutes the ‘core’ are also shifting (Owen, 2020). With the emergence of a multipolar world in which numerous sites of domination exist, it is anachronistic to assume that ‘the West’ remains the only centre of knowledge production in IR.…”
Section: Complexity In Ir Knowledge Production Practicesmentioning
confidence: 99%